The Effects of Post-Coronavirus Disease-2019 Symptoms and Functional States of Patients on Quality of Life - Bahçecioğlu Turan, Gülcan; Özer, Zülfünaz; Teke, Neslihan (AVES, 2023)
Objective: This study was conducted to examine the effects of post-coronavirus disease 2019 symptoms and functional states of patients on the quality of life. Methods: This descriptive and cross-sectional study was conducted with 1646 patients in the study between September 1 and October 31, 2021. The data were collected online by sending Patient Information Form, Post-Coronavirus Disease 2019 Symptom Form, Post-Coronavirus Disease 2019 Functional Status Scale, and the reliability of the short form 12 (SF-12) Quality of Life Scale. Results: The symptoms most experienced by the patients in the study were fever (84.7%), headache (83.7%), muscle or joint pain (83.7%), fatigue (83.5%), and cough (82.8%). In terms of coronavirus disease 2019 functional states of the participants, it was found that 23.1% responded as “Limitations in my daily life and occasional need to avoid or decrease ordinary activities,” 22.1% responded as “Limitations in my daily life and cannot perform any of the usual activities.” SF-12 physical sub-dimension mean score was found as 38.1 ± 10.38, while SF-12 mental sub-dimension mean score was found as 42.28 ± 10.38. It was found that the variable of “no limitations in daily life” had a positive effect on SF-12 physical and mental factors, while the variables of age, having limitations in daily life and not being able to perform usual activities, being dependent on someone else due to symptoms, cough, decrease in appetite, drowsiness and dizziness while standing, sleep problems, fever, body rash, and hair fall has a negative and significant effect on SF-12 physical and mental factors. Conclusion: Patients experience limitations in functional states and have a low quality of life in physical and mental dimensions due to post-coronavirus disease 2019 restrictions in daily life. Having limitations in daily life and not being able to perform usual activities, depending on someone else due to symptoms, and ongoing symptoms (cough, decreased appetite, drowsiness and dizziness while standing, sleep problems, fever, body rash, and hair loss) affect the quality of life negatively. © 2023 Sociedad Madrinela de Neumologia y Cirugia Toracica. All rights reserved.
Keywords: Functional state; post-COVID-19; quality of life; symptom